Ethical aspects of malaria control and research. (December 2015) - Jamrozik, Euzebiusz; Fuente-Núñez, Vânia; Reis, Andreas; Ringwald, Pascal; Selgelid, Michael
Abstract Malaria currently causes more harm to human beings than any other parasitic disease, and disproportionally affects low-income populations. The ethical issues raised by efforts to control or eliminate malaria have received little explicit analysis, in comparison with other major diseases of poverty. While some ethical issues associated with malaria are similar to those that have been the subject of debate in the context of other infectious diseases, malaria also raises distinct ethical issues in virtue of its unique history, epidemiology, and biology. This paper provides preliminary ethical analyses of the especially salient issues of: (i) global health justice, (ii) universal access to malaria control initiatives, (iii) multidrug resistance, including artemisinin-based combination therapy (ACT) resistance, (iv) mandatory screening, (v) mass drug administration, (vi) benefits and risks of primaquine, and (vii) malaria in the context of blood donation and transfusion. Several ethical issues are also raised by past, present and future malaria research initiatives, in particular: (i) controlled infection studies, (ii) human landing catches, (iii) transmission-blocking vaccines, and (iv) genetically-modified mosquitoes. This article maps the terrain of these major ethical issues surrounding malaria control and elimination. Its objective is to motivate further research and discussion of ethical issues associated with malaria—and to assist health workers, researchers, and policy makers in pursuit of ethically sound malaria control practice and policy.